Variational analysis to fourth-order impulsive differential equations - Saeid Shokooh (Boletim da Sociedade Paranaense de Matemática, 2018)
Applying two critical point theorems, we prove the existence of at least three solutions for a one-dimensional fourth-order impulsive differential equation with two real parameters.